The Effect of the Training Model and Balance on Students' Sepak Sila Skills on Sepak Takraw Extracurricular in First Middle School - Yudanto Yudanto; Dewangga Yudhistira; Muhammad Sigit Antoni; Mymo Septian (OVS LLC, 2022)
Study purpose. This study aimed to examine the wall and pair models: (1) the difference in the effect of wall and pair exercises on Sepak sila (2) the difference between the high and low balance on Sepak sila (3) the interaction of wall and pair models with a high and low balance on Sepak sila skills. Materials and methods. The method used in this research was a 2x2 factorial experiment. The research participants included 24 male students who took extracurricular sepak takraw aged 14-15 years with a height of 153-170± centimeters and a weight of 50-60 kilograms. The instruments used in this study were modified bass test balance instruments and Sepak sila instruments. Data collection techniques consisted of observation and tests. The data obtained were analyzed using a two-way Anova with the help of SPSS 20. Results. (1) There was a significant difference in effect between the wall and pair training models on Sepak sila skills with F 19.698 and sig. 0.000 <0.05. Based on the findings, the paired model was found to be better with an average of 46.17 compared to the model on the wall which obtained an average of 41.50. (2) It was found that there was a significant difference in effect between the high and low balance on Sepak sila skills where high balance was better with an average of 46.33 compared to low balance with an average of 41.33. (3) It was found that there was a significant interaction between the wall-mounted and paired exercise models with a high and low balance on Sepak sila skills with F 130.251 and sig. 0.000<0.05. Conclusions. In conclusion, the paired exercise model is better than the wall exercise model. As a result, it is advised to use a paired model to strengthen the fundamental technical skills of Sepak sila.